Efficient and Stable Inverted Perovskite Solar Cells with Graphene Oxide‐Modified Hole Transport Layer. Issue 11 (24th August 2022) - Chen, Yuanyuan; Cheng, Zhendong; Qiao, Feiyang; Gao, Chao; Zhang, Dezhao; Wang, Yangrunqian; Wang, Xin; Liang, Jinjin; Liu, Hong; Shen, Wenzhong
Abstract : PTAA is widely applied as an ideal organic hole‐conducting material in perovskite solar cells (PSCs) and other advanced solar cells. However, its hydrophobicity makes it hard to be compatible with the adjacent perovskite. Herein, graphene oxide (GO) as an effective modifier for the PTAA layer in PSCs is introduced. Evidently, the surface wettability of PTAA and thus the morphology and quality of the as‐formed perovskite can be well controlled by tuning the conditions of GO treatment. Furthermore, characterization of optical and electrical properties shows significant passivation effect in the interface between PTAA and the absorber. As a result, the power conversion efficiency (PCE) of the device increases from 16.21% to 17.73% after GO treatment, with almost hysteresis‐less J–V characteristics. What's more, long‐term tests also indicate significant stabilization effect in the solar cells, with the PCE of encapsulated device being retained at 99.6% of the initial value after 42 days, while the reference device retains only 80.7%. Herein, new perspectives for more efficient and stable PSCs in the view of interface modification are provided. Abstract : Graphene oxide has been applied and proved a controllable modifier for the surface property of PTAA hole transporter that can also effectively passivate the adjacent perovskite layer, with optimized efficiency increased from 16.21% to 17.73% and long‐term stability of encapsulated device that remained 99.6% of initial efficiency after 42 days of exposure to the environment.